The analysis method results in differences in the evaluation of drop jump kinetics: Proof of concept at three dropping heights - Chalitsios, C.; Panoutsakopoulos, V.; Kollias, I. A. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
The purpose of the study was to examine possible variations in estimating the initial DJ conditions (landing velocity) and consequently drop jump (DJ) performance and kinetics when using different force-recording instrumentation (i.e., number of force-plates) and analysis methods. Volleyball players (n = 10) executed DJs from 20, 40, and 60 cm. Differences in drop (DropH) and jump (Hjump) height, and DJ biomechanical parameters were examined with the nominal single (SFP) and double force-plate method (DFP), as well as the drop (DTM) and flight time (FTM) method. Results indicated that DropH was different than the nominal when the DFP and DTM were applied, leading to absolute percentage differences in Hjump ranging from 16.1% to 26.6% across drop heights. Sports scientists are suggested to use DFP for accurately measuring the initial DJ conditions.